Mediaevalism and Modernism - Tyrrell, George (Harvard theological review, 1908)
”Modernism” has already become as vague and ambiguous a term as Socialism. The latter stands for anything between common Christian charity—a recognition of social duties acknowledged by all and neglected by most—and a systematic reconstruction of the whole framework of society. Similarly, Modernism, thanks largely to the Encyclical Pascendi, has come to stand for the mildest as well as for the extremist concessions of Roman Catholicism to the exigencies of modern life and thought and sentiment. Owing to this comprehensiveness, it is possible to group together in one unholy fraternity, and under the same anathema, those who are sincere Catholics by conviction and those who, having lost all faith in the Church, continue Catholics in name and profession, whether through indifference, or self-interest, or consideration for the feelings of others. Men whose modernity is little more than an educated Ultramontanism are thus brought under suspicion of a secret sympathy with deists, atheists, and agnostics, and held up to the odium of the faithful at large.